Adressing the impact of structural fragmentation on aspects of the management and conservation of cultural heritage - Sibayi, Dumisani (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2009.